GRADUAL TRANSITION DETECTION FOR VIDEO PARTITIONING USING MORPHOLOGICAL OPERATORS - Naranjo, Valery; Angulo, Jesús; Albiol, Antonio; Mossi, Jose M; Albiol, Alberto; Gómez, Soledad (Image Analysis and Stereology, 2011)
Temporal segmentation of video data for partitioning the sequence into shots is a prerequisite in many applications: automatic video indexing and editing, old flm restoration, perceptual coding, etc. The detection of abrupt transitions or cuts has been thoroughly studied in previous works. In this paper we present a scheme to identify the most common gradual transitions, i.e., dissolves and wipes, which relies on mathematical morphology operators. The approach is restricted to fast techniques which require low computation (without motion estimation and adapted to compressed sequences) and are able to cope with random brightness variations (often occurring in old flms). The present study illustrates how the morphological operators can be used to analyze temporal series for detecting particular events, either working directly on the 1D signal or building an intermediate 2D image from the 1D signals to take advantage of the spatial operators.